Glacial meltwater and sea ice meltwater in the Prydz Bay, Antarctica - 蔡平河; 黄奕普; 陈敏; 刘广山; 邱雨生; 陈性保; 金德秋; 周锡煌 (中国科学院, 2003)
Measurements of d D and salinity were carried out in the Prydz Bay during two Antarctic cruises, the 13th and the 14th Chinese National Antarctic Research expeditions (CHINARE). Mass balance calculations based on d D and salinity showed that during the 13th CHINARE cruise, per- centages of glacial meltwater and sea ice meltwater in the study region ranged from 0% to 3.82% and from 3.19% to 4.78%, respectively. Meanwhile, the percentages were 1.53%—3.98% and 3.80%—4.52% during the 14th CHINARE cruise. We dep.